KOMPARASI FEMINISME PADA PUISI WENI SURYANDARI DAN RUPI KAUR - Faridah, Siti; Hartati, Dian (SEBASA Jurnal Pendidikan Bahasa dan Sastra, 2022)
The purpose of this study is to describe a comparison of feminist views on two poems by Indonesian poets and Indian poets. The poems compared by the researchers include the title "Perempuan Perkasa" written by Weni Suryandari and the poem entitled "Kaur a Woman of Shiki" written by the Indian poet Rupi Kaur. The approach used is comparative literature, which is an attempt to compare two or more literary works from different countries, such as two works of poetry from Indonesia and India. This research is a comparative study with the object of research in the form of feminism views contained in the two poems. The data collection method used in this research is the documentation method. The results of the research on Weni Suryandari's poetry introduce an assumption that a woman has extraordinary strength, she is able to be a man's support and even a woman can protect a man. Meanwhile, Rupi Kaur's poetry shows that women have freedom and women also have the ability to be pillars of those around them.  Keywords: Literature Comparative, Feminism, Poetry